A Study on the Efficacy of Immunotherapy with Purified Protein Derivative for the Treatment of Recalcitrant Warts - Puri, Neerja (Nepal Journal of Dermatology, Venereology & Leprology, 2017)
Introduction: There are many treatment modalities of warts, but most of them are destructive therapies which have propensity to cause scarring. Many antigens especially purified protein derivative (PPD) of tuberculin bacilli are being used for the regression of warts. Aims: To study the efficacy of purified protein derivative of tuberculin bacilli in the treatment of warts. Methods A randomized controlled trial was done in which 25 patients of recalcitrant warts were taken up for the study. In all the patients, 2.5 units of PPD was injected in each wart and upto maximum of 25 units PPD was given and the injections were given every 3 weeks for a total of 3 sessions. Results: Commonest type of wart seen in our study was verruca vulgaris in 15(60%) patients, verruca plana in 5(20%) patients, palmoplantar warts in 3 (12%) patients and genital warts in 2 (8%) patients. Regarding the number of warts 15 (60%) patients had more than 20 warts, 5 (20%) patients had number of lesions between 11 – 20 and another 5(20%) patients had lesions between 1 – 10. Complete clearance of lesions after 3 sessions was seen in 18 (72%) patients, partial clearance of lesions was seen in 4 (16%) patients and no response was seen in 3 (12%) patients. Conclusion: Immunotherapy with PPD causes boosting up of the cell mediated immunity of the patients which causes spontaneous regression of the warts.